PENGARUH STRUKTUR KEPEMILIKAN, PROFITABILITAS DAN KEBIJAKAN KEUANGAN TERHADAP NILAI PERUSAHAAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019) - Ramadhani, Nadya Shafira; Subaki, Ahmad; Sonjaya, Ahmad (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACTThis study aims to determine how the influence of ownership structure, profitability, dividend policy, debt policy and investment policy on company value in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. In this research, the method of explanation is used. The variables in this study are managerial ownership structure (X1), profitability (X2), dividend policy (X3), debt policy (X4), investment policy (X5) and firm value (Y). The population of this research is manufacturing companies listed on the Indonesia Stock Exchange. The sample selection technique used was purposive sampling. The results of this study indicate that partially managerial ownership has no effect on firm value. Profitability variable partially affects firm value. Dividend policy variable partially has no effect on firm value. The debt policy variable partially affects firm value. The investment policy variable partially affects firm value.